Respostas
respondido por:
8
a = 1; b = 3; c = -10
Para que f(x) seja igual a zero, devemos determinar suas raízes.
Δ = (3)² - 4*1* (-10)
Δ = 9 + 40
Δ = 49
1)![\frac{3 + 7}{2} = 5 \frac{3 + 7}{2} = 5](https://tex.z-dn.net/?f=+%5Cfrac%7B3+%2B+7%7D%7B2%7D+%3D+5+)
2)![\frac{3 - 7}{2} = -2 \frac{3 - 7}{2} = -2](https://tex.z-dn.net/?f=+%5Cfrac%7B3+-+7%7D%7B2%7D+%3D+-2+)
Para f(x) = 6, basta seguir o mesmo procedimento!
f(x) = x² + 3x - 10 = - 6
f(x) = x² + 3x - 4 = 0
Δ = 9 - 4 * 1* (-4)
Δ = 25
1)![\frac{-3 + 5}{2} = 1 \frac{-3 + 5}{2} = 1](https://tex.z-dn.net/?f=+%5Cfrac%7B-3+%2B+5%7D%7B2%7D+%3D+1+)
2)
Para que f(x) seja igual a zero, devemos determinar suas raízes.
Δ = (3)² - 4*1* (-10)
Δ = 9 + 40
Δ = 49
1)
2)
Para f(x) = 6, basta seguir o mesmo procedimento!
f(x) = x² + 3x - 10 = - 6
f(x) = x² + 3x - 4 = 0
Δ = 9 - 4 * 1* (-4)
Δ = 25
1)
2)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás